Follistatin preferentially antagonizes activin rather than BMP signaling in Drosophila. - Pentek, J.; Parker, L.; Wu, A.; Arora, K. (genesis, 2009)
Ligands of the transforming growth factor-beta (TGF-beta) superfamily play important roles in embryonic patterning and development throughout the animal kingdom. Consequently, extracellular factors that affect ligand stability, mobility, and receptor interaction also have profound effects on development. One such regulator, Follistatin (Fst), functions as an inhibitor of both activin and bone morphogenetic protein (BMP) subfamilies of TGF-beta ligands in vertebrates. Drosophila follistatin (fs) encodes a Fst homolog that is broadly expressed throughout development, but the in vivo function of the protein remains unclear. We show that overexpression of fs affects prepupal to pupal transition and morphogenesis, highlighting a novel requirement for TGF-beta signaling in metamorphosis. In addition, fs expression disrupts various aspects of neuronal morphogenesis, mimicking mutant phenotypes of the activin ligands, Dawdle (Daw) and Activin-beta. In assays targeting endogenous BMP signaling, we find no evidence that fs can antagonize BMP activity. We conclude that fs functions primarily as an inhibitor of activin rather than BMP ligands.